The TORCH time-of-flight detector for particle identification and photon vertex association. (2nd February 2017) - García, L. Castillo; Brook, N.; Cussans, D.; Föhl, K.; Forty, R.; Frei, C.; Gao, R.; Gys, T.; Harnew, N.; Piedigrossi, D.; Rademacker, J.; García, A. Ros; et al.
Abstract: TORCH (Time Of internally Reflected CHerenkov light) is a novel time-of-flight detector, designed to provide π /K/p particle identification up to 0∼ 1 GeV/c momentum and beyond. To achieve this, a time resolution of ∼ 15 ps combining information from 0∼ 3 detected photons is required over a 10 m flight path. Large areas can be covered with TORCH, nominally up to 30 m 2 . One such application is for the LHCb experiment, to complement the particle identification capabilities of its RICH detectors. TORCH has a DIRC-like construction with 10 mm-thick synthetic amorphous fused-silica plates as a radiator. Cherenkov photons propagate by total internal reflection to the plate edges and there are focussed onto an array of position-sensitive photodetectors. Custom-built micro-channel plate photo-multipliers (MCP-PMTs) are being developed in collaboration with industry to provide the lifetime, granularity and time resolution to meet the TORCH specifications. In the present paper, laboratory tests of the MCP-PMTs developed for TORCH and its readout electronics are presented. Test beam measurements of a prototype TORCH detector in a low-momentum mixed beam of pions and protons are highlighted. Time resolutions for individual photons approaching 100 ps is achieved, after correction for dispersion effects in the quartz medium. In addition to the particle identification capabilities, the high-precision timing information that TORCH provides could be used at the high-luminosity LHC to associate high-energy photons with the correct primary interaction vertex amongst the many expected.